Statistical Study on the Incidence of Disease and Psychological Stress on Health - Dalal Naji Ajeel Abd; Zainab Murtadha Mustafa Benjah; Eadi Samie Najm Abdullah; Zahraa Imad Aboud Hassan; Israa Mahmoud Hassan Mohammed; Zainab Abdul Nabi Thamer Karim (American Journal of Biomedicine and Pharmacy, 2024)
Through the results of the practical application, the following conclusions were reached: From Table (1), it was found that there is a significant relationship between age and continuous stress that affects heart health. From Table (2), it was found that there is a significant relationship between nervous stress affecting mood and psychological pressures and thinking about it a lot leads to feeling tired. From Table (3), it was found that there is a significant relationship between psychological pressures and thinking about it a lot leads to feeling tired and nervous tension is not a dangerous matter. From Table (4), it was found that there is a significant relationship between a person who feels stressed and psychological pressure that keeps him alone until he calms down and stress and pressure lead to insomnia or lack of sleep. From Table (5), it was found that there is a significant relationship between stress and pressure that leads to insomnia or lack of sleep and stress and psychological pressures affect work productivity. From Table (6) it is clear that there is a significant relationship between stress and pressure leading to insomnia or lack of sleep and exercising or physical activity relieves stress. From Table (7) it is clear that there is a significant relationship between the increased chances of infection in the event of feeling due to a lack of immunity and some people feel toothache as a result of stress. From Table (8) it is clear that there is a significant relationship between the effect of stress and psychological pressures on work productivity and psychological stress can negatively affect physical health. From Table (9) it is clear that there is a significant relationship between exercising or physical activity relieves stress and stress and psychological pressure lead to difficulty in concentrating. From Table (10) it is clear that there is no significant relationship between psychological stress can negatively affect physical health and continuous stress affects heart health. From Table (11) it is clear that there is no significant relationship between gender and nervous tension affects mood.